An IoT Framework for Addressing Parents Concerns about Safety of School Going Children - Poonam Gupta; D D Shah; K V V Satyanarayana (International Journal of Electrical and Computer Engineering (IJECE), 2016)
In this paper, we have proposed a novel application using Internet of things (IOT). This application is focused to address the concerns of the parents towards their school going kids. Mainly the concerns of the parents are to ensure the safety of their kids in school bus as well as at school premises. In this paper, we have tried to provide detailed technical implementation about how different sensing, communication technologies clubbing together provides a platform in terms of IoT, where proposed application can be implemented to ensure safety of school going children as it is the priority and concern for parents. In Proposed application, parents get notification when his child boards the bus for school and gets down the bus at home’s doorstep. Parents also get notification when child enters his Class Room first time in a day. Parents any time can access the location his child or school bus in which his child is travelling. In case of emergency, child can disseminate the signal to parents / Single point of contact (SPOC) at school to make them aware about emergency.